Beyond Theory: A UX Outcomes Casebook for HCI Education - Hillman, Serena; Pang, Carolyn; Jain, Samira; Neustaedter, Carman; Kaye, Jofish; Rizvi, Ali; McDonald, David; Wu, Qunfang; MacDonald, Craig (2024 International Conference on Human-Computer Interaction, 2024)
The CHI community has expressed a growing interest in creating and sharing educational materials related to User Experience (UX) outcomes, particularly emphasizing summative research. Based on insights gathered at a CSCW 2003 workshop on understanding and evaluating UX outcomes at scale, we identified two areas of focus: (1) the need to develop Human-Computer Interaction (HCI) educational resources for UX, specifically focusing on summative methods and industry practices, and (2) the opportunity to further review and discuss the potential of a casebook—a textbook centered around case studies. This Special Interest Group (SIG) at CHI 2024 aims to directly address these opportunities by bringing together a community of academic and industry researchers for the exchange of ideas, ultimately guiding the development of educational resources that equip HCI students with strong summative research skills as they enter the UX field. At the SIG, we will discuss HCI educational resources for UX outcomes and present a casebook outline, gathering feedback, insights, and interest regarding the proposed case studies and general format.